2015
DOI: 10.1371/journal.pone.0122114
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Diffusivity in Multiple Sclerosis: Analysis of Optic Radiation Lesional and Non-Lesional White Matter

Abstract: ObjectivesDiffusion tensor imaging (DTI) has been suggested as a new promising tool in MS that may provide greater pathological specificity than conventional MRI, helping, therefore, to elucidate disease pathogenesis and monitor therapeutic efficacy. However, the pathological substrates that underpin alterations in brain tissue diffusivity are not yet fully delineated. Tract-specific DTI analysis has previously been proposed in an attempt to alleviate this problem. Here, we extended this approach by segmenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 83 publications
4
54
0
1
Order By: Relevance
“…29 Similarly, in patients with relapsing-remitting multiple sclerosis, tract-specific DTI analysis of the optic radiations showed selective increases in RD only within the T2 lesions and, therefore, related to local myelin disruption. 30 The absence of demyelination at postmortem examination in one of our patients with MNGIE as well as in the other 2 previously reported cases 14 points to increased intramyelin water content as the most likely explanation for prominent or selective radial diffusivity found in brain white matter structures in our patients. A negative correlation between N-acetylaspartate concentration and mean diffusivity values within the same white matter volume was demonstrated, supporting the hypothesis of a dilution effect as the basis of the metabolite concentration reduction, possibly affecting neuronal cells, because no correlation was observed between any other metabolite concentration expressed in either neural or glial cells and any DTI metrics.…”
Section: Discussionsupporting
confidence: 64%
“…29 Similarly, in patients with relapsing-remitting multiple sclerosis, tract-specific DTI analysis of the optic radiations showed selective increases in RD only within the T2 lesions and, therefore, related to local myelin disruption. 30 The absence of demyelination at postmortem examination in one of our patients with MNGIE as well as in the other 2 previously reported cases 14 points to increased intramyelin water content as the most likely explanation for prominent or selective radial diffusivity found in brain white matter structures in our patients. A negative correlation between N-acetylaspartate concentration and mean diffusivity values within the same white matter volume was demonstrated, supporting the hypothesis of a dilution effect as the basis of the metabolite concentration reduction, possibly affecting neuronal cells, because no correlation was observed between any other metabolite concentration expressed in either neural or glial cells and any DTI metrics.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, a linear regression model was employed that, apart from lesion volume, also included disease duration, age, gender, and a history of ON. The model explained 38% of the observed increase in RD in non-lesional fibers and demonstrated a significant effect of T2 lesion volume outside of the OR and, to a lesser extent, disease duration and history of ON on RD [91]. The same investigators reported significant associations between mfVEP latency delay and increased ORspecific T2 lesion volume.…”
Section: Optic Radiation Dtimentioning
confidence: 80%
“…One study reported regional RD elevation in the OR parts that were affected by OR-specific white matter lesions corroborating the role of RD as a potential marker for demyelination [91]. A significant elevation of RD in OR non-lesional fibers that correlated with increased global but not focal T2 lesion volume was found, possibly indicating OR fiber damage to be related to the overall burden of brain inflammatory activity [91]. In this study, a linear regression model was employed that, apart from lesion volume, also included disease duration, age, gender, and a history of ON.…”
Section: Optic Radiation Dtimentioning
confidence: 86%
See 1 more Smart Citation
“…28 The Glu increase during the pre-lesional period was strongly correlated with the AD increase, which is generally deemed to relate to axonal injury. 4,5,[29][30][31] The early pathological changes discussed above may therefore be indicative of the extent of eventual axonal damage within newly developing WM lesions in MS. Moreover, a stronger increase of Glu in pre-lesional WM was also associated with higher subsequent lesion volumes.…”
Section: Pre-lesional Periodmentioning
confidence: 99%